Identification of Potential Groundwater Recharge Zones Using GIS Based Multi-Criteria and AHP Technique: A Case Study of Pune City, Western Maharashtra: 10.32526/ennrj/21/202200257 - Vaddadi, Natraj; Vansarochana, Chaiwiwat; Raghavan, Venkatesh (Environment and Natural Resources Journal, 2023)
With dwindling supply of surface water, Ground water is increasingly being used as a source of fresh water in many cities across the world. Consequently, there is an increasing need to evaluate groundwater potential of an area. Over the past few decades, Remote Sensing and GIS have been used for systematic investigations on potential recharge of aquifers. As in major cities of the world, the demand for water in Pune City is also increasing every year and demand outstrips the supply of surface water. This study delineated potential zones for artificial recharge across Pune City by using Multi-criteria analysis and the Analytical Hierarchy Process (AHP) techniques. Artificial recharge techniques especially the use of rainwater harvesting (RWH) are being deployed globally to augment supply of fresh water. Ground-water recharge is directly influenced by surface characteristics such as rainfall, geology, soil types, Land Use/Land Cover (LULC), drainage, lineaments/fractures, etc. Hence, six such parameters, namely, LULC, Slope, Soil texture, Rainfall, Drainage density, and Geology were considered to generate a groundwater recharge potential map. Based on the analysis, the study area was zoned into five classes, namely, low, moderate, good, very good and high groundwater potentials. About 45% of the city shows good to high potential for recharge. The results reveal that the high and good potential recharge zones lie to the western part of the city, whereas the central part (inner city) and the eastern part show medium to low potential for recharge. The results can help to identify areas for recharge and formulate a framework for systematic recharge of the existing aquifers in the area under study.